Frog tongue surface microstructures: functional and evolutionary patterns - Thomas Kleinteich (Beilstein Journal of Nanotechnology, 2016)
Frogs (Lissamphibia: Anura) use adhesive tongues to capture fast moving, elusive prey. For this, the tongues are moved quickly and adhere instantaneously to various prey surfaces. Recently, the functional morphology of frog tongues was discussed in context of their adhesive performance. It was suggested that the interaction between the tongue surface and the mucus coating is important for generating strong pull-off forces. However, despite the general notions about its importance for a successful contact with the prey, little is known about the surface structure of frog tongues. Previous studies focused almost exclusively on species within the Ranidae and Bufonidae, neglecting the wide diversity of frogs. Here we examined the tongue surface in nine different frog species, comprising eight different taxa, i.e., the Alytidae, Bombinatoridae, Megophryidae, Hylidae, Ceratophryidae, Ranidae, Bufonidae, and Dendrobatidae. In all species examined herein, we found fungiform and filiform papillae on the tongue surface. Further, we observed a high degree of variation among tongues in different frogs. These differences can be seen in the size and shape of the papillae, in the fine-structures on the papillae, as well as in the three-dimensional organization of subsurface tissues. Notably, the fine-structures on the filiform papillae in frogs comprise hair-like protrusions (Megophryidae and Ranidae), microridges (Bufonidae and Dendrobatidae), or can be irregularly shaped or absent as observed in the remaining taxa examined herein. Some of this variation might be related to different degrees of adhesive performance and may point to differences in the spectra of prey items between frog taxa.